Answer with Step-by-step explanation:
Let ?=x
We have to find the value of x in:
[tex](-b^3+3b^2+8)-(x-5b^2-9)=5b^3+8b^2+17[/tex]
Adding [tex]b^3[/tex] on both sides, we get
[tex]-b^3+3b^2+8-x+5b^2+9+b^3=5b^3+8b^2+17+b^3[/tex]
[tex]3b^2+8-x+5b^2+9=5b^3+8b^2+17+b^3[/tex]
Combining the like terms on both side, we get
[tex]8b^2+17-x=6b^3+8b^2+17[/tex]
Subtracting both sides by 8b², we get
[tex]8b^2-x+17-8b^2=6b^3+8b^2+17-8b^2[/tex]
[tex]-x+17=6b^3+17[/tex]
subtracting both sides by 17, we get
[tex]-x+17-17=6b^3+17-17[/tex]
[tex]-x=6b^3[/tex]
Dividing both sides by -1, we get
[tex]x=-6b^3[/tex]
Hence, ? = [tex]-6b^3[/tex]